Evaluating Financial Performance Based On Environmental Performance, Environmental Costs, and Environmental Disclosure - Safitri, Nabila; Hadiwibowo, Imam; Azis, Mohammad Taufik (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study examines the relationship between environmental performance, environmental costs, and environmental disclosures with financial performance among companies in the basic materials and consumer non-cyclical sectors listed on the Indonesia Stock Exchange from 2021-2023. Utilizing a quantitative approach with multiple linear regression analysis, the study reveals that environmental disclosure positively impacts financial performance, while environmental performance and environmental costs show no significant effect. The findings indicate that transparent sustainability reporting enhances stakeholder confidence and company reputation, contributing to improved financial outcomes. The results align with legitimacy theory, emphasizing the importance of aligning corporate activities with societal norms to achieve long-term financial stability. Despite the increasing global emphasis on sustainability, the study underscores the need for greater public awareness and investment in environmental initiatives to realize their full financial benefits.